Institutional Regulation of the CIS Observer Mission in Election Campaigns and Coverage of Its Activities in the Media - S. A. Malinina (Евразийская интеграция: экономика, право, политика, 2024)
This study is aimed at studying the institutional, organizational and legal problems of interaction between the media and international observers during elections and referendums in the member states of the Commonwealth of Independent States. The issue of countering foreign interference in the electoral process was not considered in the work.Aim. Eliminate methodological problems in defining the content of the term “international observation”, and proving the need to institutionalize the process of covering the activities of international observers in the media.Tasks. Identify the necessary areas of media activity when covering the activities of international observers during elections and referendums.Methods. The state of the modern election monitoring environment indicates the existence of a fine line between the need to ensure openness of electoral processes and the inadmissibility of interference in the internal affairs of states. It is necessary to identify restrictive thresholds for the activities of the media when covering the processes of international observation of elections and referendums and their institutionalization in relevant advisory documents based on the presumed impartiality of both international observers and the media.Results. The study showed that the most important task of the process of legitimizing the electoral process is to ensure its full coverage of the activities of all its subjects in the media. International monitoring media coverage should cover a wide range of issues throughout the entire electoral process from start to finish, including; activities of observers during the official election campaign before the start of voting; on election day and during the vote counting process; in the period after the elections from the moment the official results are announced until the formation of new authorities. At the same time, at all stages, coverage should cover a wide range of issues of the essence of the electoral process and its management; legal regulation of elections and referendums and existing institutional structures to support the process.Conclusions. Media coverage of the activities of international observers should be considered not only as one of the most important modes of political communication, but also as a means of countering selective absenteeism. Objective and impartial coverage of the activities of international observers in the media can undoubtedly contribute to both the internal political mobilization of the population and the international recognition of the state.